Perbandingan Algoritme FIFO, PIE, dan RED terhadap Quality of Service pada Wireless Local Area Network - Rayza Arfian; Primantara Hari Trisnawan; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One product of technological advancements in wireless network is Wi-Fi with the IEEE 802.11 standard. Wi-Fi technology can be found in public facilities in the form of a Wireless Local Area Network (WLAN) and then turned into a public hotspot. A public hotspot surely has limitation either in accomodating a data packet or a number of clients connected. Data packets that are in the queue are generally processed according to the order in which the packets arrives. This can have an effect on Quality of Service. In this research, the implementation of the queue algorithm in the WLAN was carried out to determine its effect on Quality of Service. The queue algorithms are the First-In-First-Out (FIFO) algorithm, Enhanced Proportional Integral Control (PIE), Random Early Detection (RED). The Wi-Fi standard being used is IEEE 802.11b. In Packet Delivery Ratio, the FIFO algorithm provides better results than PIE and RED. FIFO experienced a 0,7% improvement when using 1000 packets as a queue capacity. Then in the End-to-End Delay test, PIE and RED provide an average delay of 0,9 seconds on each test, better than the FIFO algorithm which can reach 5 seconds. Finally, in throughput all the algorithms tested give results that are not far with only 1-2 bps differences.